2006
DOI: 10.1111/j.1463-1326.2006.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin detemir improves glycaemic control with less hypoglycaemia and no weight gain in patients with type 2 diabetes who were insulin naive or treated with NPH or insulin glargine: clinical practice experience from a German subgroup of the PREDICTIVE study*

Abstract: These data confirm the short-term safety and efficacy of insulin detemir +/- OADs in a real-world scenario and support the findings of randomized controlled clinical trials with insulin detemir, including its limited effects on body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 28 publications
3
55
2
2
Order By: Relevance
“…Adjustment for change in HbA1c did not affect the finding [78]. In a subgroup analysis of the PREDICTIVE study evaluating individuals in a clinical practice setting who transferred from an OAD-only regimen to an OAD plus insulin detemir, NPH insulin or insulin glargine, all subgroups combined lost an average of 0.9 kg of body weight (p < 0.0001) [47].…”
Section: Conventional Antidiabetic Therapeutics: Impact On Weightmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjustment for change in HbA1c did not affect the finding [78]. In a subgroup analysis of the PREDICTIVE study evaluating individuals in a clinical practice setting who transferred from an OAD-only regimen to an OAD plus insulin detemir, NPH insulin or insulin glargine, all subgroups combined lost an average of 0.9 kg of body weight (p < 0.0001) [47].…”
Section: Conventional Antidiabetic Therapeutics: Impact On Weightmentioning
confidence: 99%
“…Adjustment for change in HbA1c did not affect the finding [78]. In a subgroup analysis of the PREDICTIVE study evaluating individuals in a clinical practice setting who transferred from an OAD-only regimen to an OAD plus insulin detemir, NPH insulin or insulin glargine, all subgroups combined lost an average of 0.9 kg of body weight (p < 0.0001) [47].The clinical efficacy of rosiglitazone and pioglitazone as monotherapy or combination therapy with insulin, sulphonylureas or metformin is well established [79][80][81]. A class effect of TZDs, however, is treatment-associated weight gain and large, longitudinal studies such as ADOPT, DREAM and PROactive have shown that these agents can cause appreciable weight gain of up to 4-5 kg [41,42,44].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In randomized clinical trials (RCTs) in insulin-naïve people with T2D, basal insulin analogs have demonstrated better glycemic control with a lower risk of hypoglycemia compared with human neutral protamine Hagedorn (NPH) insulin [13][14][15][16][17][18] . Furthermore, the clinical effectiveness of basal insulin analogs in T2D has been demonstrated in real-life observational studies 5,[19][20][21][22][23] . Observational data are often collected from large heterogeneous populations that help enhance the generalizability of the clinical findings of RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…The insulin analogue insulin detemir causes fewer hypoglycaemic events and less weight gain, leading to improvements in quality adjusted life-years (QALYs) compared with NPH insulin 21,22 .…”
mentioning
confidence: 99%